Pancreatic fibroblast growth factor 21 protects against type 2 diabetes in mice by promoting insulin expression and secretion in a PI3K/Akt signaling‐dependent manner. Issue 2 (20th November 2018) - Pan, Yingying; Wang, Baile; Zheng, Jujia; Xiong, Rongrong; Fan, Zhichao; Ye, Yanna; Zhang, Saisai; Li, Qinyao; Gong, Fanghua; Wu, Chaoming; Lin, Zhuofeng; Li, Xiaokun; et al.
Abstract: Fibroblast growth factor 21 (FGF21) is important in glucose, lipid homeostasis and insulin sensitivity. However, it remains unknown whether FGF21 is involved in insulin expression and secretion that are dysregulated in type 2 diabetes mellitus (T2DM). In this study, we found that FGF21 was down‐regulated in pancreatic islets of db/db mice, a mouse model of T2DM, along with decreased insulin expression, suggesting the possible involvement of FGF21 in maintaining insulin homeostasis and islet β‐cell function. Importantly, FGF21 knockout exacerbated palmitate‐induced islet β‐cell failure and suppression of glucose‐stimulated insulin secretion (GSIS). Pancreatic FGF21 overexpression significantly increased insulin expression, enhanced GSIS, improved islet morphology and reduced β‐cell apoptosis in db/db mice. Mechanistically, FGF21 promoted expression of insulin gene transcription factors and soluble N‐ethylmaleimide‐sensitive factor attachment protein receptor (SNARE) proteins, the major regulators of insulin secretion, as well as activating phosphatidylinositol 3‐kinase (PI3K)/Akt signaling in islets of db/db mice. In addition, pharmaceutical inhibition of PI3K/Akt signaling effectively suppressed FGF21‐induced expression of insulin gene transcription factors and SNARE proteins, suggesting an essential role of PI3K/Akt signaling in FGF21‐induced insulin expression and secretion. Taken together, our results demonstrate a protective role of pancreatic FGF21 in T2DM mice through inducing PI3K/Akt signaling‐dependent insulin expression and secretion.